Determinants of Six-Month Appointment Spacing Model Utilization Among ART Clients in the Public Health Facilities of Jimma Town, Southwest Ethiopia: Case–Control Study - Ragea G (Dove Medical Press, 2021)
Goshu Ragea,1 Fessahaye Alemseged2 ,† Mamo Nigatu,2 Diriba Dereje3 1Department of HIV/AIDS Prevention and Control, CDC Oromia, Jimma, Ethiopia; 2Department of Epidemiology, Jimma University, Jimma, Ethiopia; 3Department of Biomedical Science, Jimma University, Jimma, Ethiopia†Dr Fessahaye Alemseged passed away on August 7, 2020Correspondence: Goshu Ragea Email grgoshu20@gmail.comBackground: Ethiopia is currently implementing an Appointment Spacing Model (ASM) for ART. A study conducted in 6 hospitals that piloted ASM showed that 51% of eligible clients declined ASM. Studies conducted on ASM have focused on its benefits, not factors determining its utilization. This study aimed to identify determinants of ASM non-utilization.Objective: To identify determinants of ASM non-utilization among stable ART clients.Methods: An unmatched case–control study was conducted among 194 cases and 194 controls: consecutively selected stable clients on anti-retroviral therapy (ART) at four public health facilities in Jimma town. Data were collected through face-to-face interviews and observation techniques using semi-structured questionnaire and observation checklist. EpiData version 3.1 and SPSS version 23 were respectively used for data entry and analysis. Descriptive statistics, logistic regression, adjusted odds ratio and 95% CI were used to summarize descriptive data, identify determinants of ASM non-utilization, measure the strength of statistical association, and declare the statistical significance respectively.Results: With 100% response rate, predictors of ASM non-utilization were residing in urban areas (AOR=2.61, 95% CI: 1.10– 6.18), fear regarding drug safety (AOR=3.19, 95% CI: 1.56– 6.54), duration of ART (< 5 years) (AOR=2.45, 95% CI: 1.17– 5.16), need for frequent checkups (AOR=2.70, 95% CI: 1.29– 5.61), poor understanding of ASM (AOR=3.15, 95% CI: 1.54– 6.43), high perceived difficulties of engagement in ASM (AOR=10.13, 95% CI: 4.31– 23.84), perceived presence of high opportunistic cost (AOR=3.34, 95% CI: 1.64– 6.83), low self-efficacy (AOR=7.44, 95% CI: 3.16– 17.46), recent history of opportunistic infection (AOR=3.34, 95% CI: 1.64– 6.83), absence of competing family activities (AOR=4.39, 95% CI: 2.05– 9.44) and stigma (AOR=2.85, 95% CI: 1.39– 5.81).Conclusion: The majority of factors affecting ASM non-utilization were behavioral and community related, which can be addressed by health education both at client and community level and additionally, by training service providers to address factors connected with the provision of service. Qualitative study and impact assessment on client retention are recommended for further research.Keywords: ASM, HIV/AIDS, public health facility, Jimma